Immunologic and virological response to ART among HIV infected individuals at a tertiary hospital in Ghana - Obiri-Yeboah, Dorcas (BMC Infect Dis, 2018)
BACKGROUND: The need to study the outcome of Antiretroviral Therapy (ART) among Human Immunodeficiency Virus (HIV) infected individuals in Ghana, a sub-Saharan African country crucial in the era of the “Treat All” policy. The aim of this study was to analyze selected determinants of immunological and virological response to ART among HIV infected individuals in a tertiary facility in Cape Coast, Ghana. METHODS: An analytical cross sectional study with a retrospective component was conducted in the Cape Coast Teaching Hospital (CCTH), Central Region. Clients aged 18 years and above attending the HIV Clinics for ART and who were on ART for 6 months or more were recruited. The viral loads, CD4 count and other socio-demographic data were analyzed using STATA version 13 (STATA Corp, Texas USA). Descriptive analysis was done and presented with appropriate measures of central tendencies. In addition, bivariate and multivariate analysis was carried out with p value of 0.05 interpreted as evidence of association between variables. RESULTS: A total of 440 participants were included in this study with a mean age of 45.5 (±11.6) years. The mean CD4 count at baseline, 6 months on ART and currently at study recruitment were 215.1 cells/mm(3) (±152.6), 386.6 cells/mm(3) (±178.5), and 579.6 cells/mm(3) (±203.0) respectively. After 6 months and 12 months on ART, the number who had achieved viral copies < 1000/ml were 149 (47.0%) and 368 (89.6%) respectively. There was strong evidence of an association between having CD4 count < 350 cells/mm(3) after 6 months on ART and having a diagnosis of tuberculosis since HIV diagnosis (aOR 8.5, 95% CI 1.1–73.0, p = 0.05) and clients having plasma viral load > 1000 copies/ml after 6 months on ART (aOR 2.0, 95% CI 1.2–3.2, p = 0.01). CONCLUSION: There was good response to ART among clients, high virological suppression and immunological recovery hence low rates of change to second line ART regimen in this cohort studied. With strict adherence to the national policy on HIV testing, management of positive clients and full implementation of the “Treat All” policy, Ghana could achieve, if nothing at all, the third “90, 90, 90” target by 2020. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12879-018-3142-5) contains supplementary material, which is available to authorized users.